Obstacles to digital, multimodal pedagogy in rural high schools. (30th May 2018) - Howell, Emily
Abstract : The author reports findings from two iterations of a formative experiment focusing on improving students' conventional and digital, multimodal arguments. The first iteration of this experiment occurred in a rural school district in the United Sates with an eleventh-grade English/language arts teacher, and the second iteration was implemented in the same school district, but in a different high school with both a ninth- and tenth-grade English/language arts teacher. The findings focus upon obstacles the teachers encountered while implementing an intervention that entailed elements of argument; digital, multimodal tools; and the writing process. These obstacles led the author to make six recommendations for the future professional development of rural teachers integrating digital, multimodal tools into conventional writing curriculum.